A Comparative Analysis of Risk Perception, Risk Tolerance, and Expected Return on University Students’ Interest in Online Gambling and Stock Investment - Marino, Wilman San; Badriatin, Tine; Sani, Ageng Asmara (Almana : Jurnal Manajemen dan Bisnis, 2025)
The growing participation of university students in both stock investment and online gambling raises concerns regarding how psychological factors shape financial decision-making. This study aims to examine and compare the effects of risk perception, risk tolerance, and return expectation on students’ investment decisions by distinguishing between students who invest exclusively in stocks and those who invest in stocks while engaging in online gambling. A quantitative research design was employed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess the structural relationships among the variables, complemented by independent samples t-tests to evaluate intergroup differences at the indicator level. The findings indicate that return expectation, risk perception, and risk tolerance all exert positive and significant effects on investment decisions, with return expectation emerging as the strongest predictor. However, comparative results reveal that most indicators do not differ significantly between the two groups, except for specific risk perception indicators, suggesting lower risk perception among students involved in online gambling. These results support Prospect Theory, Dual Process Theory, and Cognitive Distortion models by highlighting the role of cognitive biases and risk underestimation in gambling-related behavior. In conclusion, the study underscores the importance of financial literacy programs that emphasize accurate risk perception and cognitive debiasing strategies to mitigate students’ vulnerability to speculative and gambling-related behaviors.